Kawasaki disease: do the manifestations in children observed in the Russian Federation and in foreign countries coincide? - N. Yu. Golovanova; A. G. Samedova; Yu. O. Kostina (Лечащий Врач)
Background. Mucocutaneous lymphonodular syndrome (Kawasaki syndrome/disease) occurs most commonly in children under 5 years of age. Approximately one-third of patients who fail therapy form coronary artery aneurysms. Timely administration (before day 10 of the disease) of intravenous immunoglobulin and acetylsalicylic acid significantly reduces this probability.Objective. To assess the relationship between timely therapy with intravenous immunoglobulin and the development of coronary artery aneurysms, to analyze the effectiveness of ntravenous immunoglobulin therapy; features of gender, age differences in children with Kawasaki disease according to the database of patients from 0 to 17 years old observed in the Clinic of Children's Diseases of the Sechenov Center for Maternal and Child Health with a diagnosis of Kawasaki disease from 2010 to 2023.Study design. Retrospective cohort study.Materials and methods. This study included a consecutive sample of 104 individuals from the Kawasaki disease patient database residing in the Russian Federation. Children were observed at the Sechenov Center for Maternity and Childhood from January 1, 2010, to December 31, 2023.Results. Among 104 patients with established diagnosis of Kawasaki disease, 95 (91.3%) patients received intravenous immunoglobulin and acetylsalicylic acid, among them 37 (38.9%) children developed coronary aneurysms. Of the 9 (8.7%) patients who did not receive intravenous immunoglobulin therapy, 6 developed coronary aneurysms, 4 of which were giant. Among 43 patients with coronary aneurysms, boys predominated – 34 (79%), respectively, there were 9 (21%) girls. All patients with coronary aneurysms over 60 months were boys. Conclusion. The results obtained coincide with the data of similar studies conducted in other countries, despite, at a minimum, racial differences.